Alteration of primary cilia in COPD. Issue 1 (12th July 2018) - Perotin, Jeanne-Marie; Coraux, Christelle; Lagonotte, Eymeric; Birembaut, Philippe; Delepine, Gonzague; Polette, Myriam; Deslée, Gaëtan; Dormoy, Valérian
Chronic obstructive pulmonary disease (COPD) is a major economic and social concern worldwide because of its impact on mortality and morbidity [1]. COPD is characterised by airway epithelium remodelling, a hallmark of dysregulated airway epithelium plasticity [2]. There are currently no available therapeutics to restore the integrity and functionality of the epithelium. Therefore, novel sources of investigation are becoming crucial to understand the alterations at the root of COPD initiation. Non-motile primary cilia are solitary sensor organelles playing a critical role in cell cycle control, proliferation, polarity and differentiation, particularly of ciliated cells possessing motile cilia [3, 4]. Primary cilia are assembled on different types of human cells depending on their state and activities in response to cellular quiescence where they relay extracellular signals and retract upon cell cycle re-entry [5]. Alterations of primary cilium structure and function are responsible for ciliopathies [6, 7]. Primary cilia may be crucial in determining outcomes during airway epithelial cell differentiation thus we hypothesised that primary cilia are present in adult epithelial cells and may play a key role in airway plasticity. First, we investigated the presence and localisation of primary cilia in the bronchial epithelium. Secondly, we analysed the relationships between primary cilia and clinical, functional and histological characteristics of non-COPD and COPD patients. Non-differentiated airway epithelial cells display primary cilia and their number is associated with COPD features http://ow.ly/wiGH30jDbeG